Users’ Information Requirements and Narrative Reporting: The Case of Iranian Companies - Bikram Chatterjee; Soheila Mirshekary; Omar Al Farooque; Maryam Safari (Australasian Accounting, Business and Finance Journal, 2010)
This paper investigates whether the narrative section of Iranian companies’ annual reports satisfies the information requirements of financial analysts employed by institutional investors. Taking a group of stakeholders (i.e. financial analysts) as the sample, a questionnaire survey was conducted to identify their top three information needs from the narrative sections of company annual reports in each of three information categories: Present, Analytical and Prospective. Following this survey, a checklist was prepared to analyse whether Iranian companies are disclosing this information required by financial analysts. Overall, the results partially support stakeholder theory as there is a general lack of information flow on the part of Iranian listed companies in meeting their stakeholders’ information needs.
Keywords: Annual Reports; Narrative sections; Users’ information needs; Iranian companies